Políticas públicas e território: a experiência de gestão territorial dos Centros de Referência de Assistência Social do Município de Belo Horizonte - Souza, Soraia Pereira de (2017)
This dissertation analyzes the experience of territorial management of the Centers of Reference of Social Assistance - CRAS from Belo Horizonte with the objective of identifying the main factors involved in the exercise of territorial management in the municipality. The incorporation of the socio-territorial dimension, inserted in the management model prescribed in the normative bases of the Single System of Social Assistance - SUAS, involves significant changes in the way of conceiving and operationalizing social protection in the social assistance policy. So, the territorial approach assumes strategic importance both to understand the social dynamics that lead different populations to situations of vulnerability and social risk as it comes to be perceived as a privileged space of organization, coordination and management. For these reasons, assuming the territory as a place of organization and intervention, a new way of thinking about the social protection model in the social assistance policy is inaugurated, which has generated great expectations about Basic Social Protection and CRAS performance as an equipment capable of valuing participatory arrangements, strengthening family and community ties, and mobilizing through interaction and articulation with other actors and services. Identifying the factors that interfere in the territorial management of the CRAS in the mentioned municipality, it is expected that such an approach may contribute to the improvement of this mechanism, provided for by the recently institutionalized National Social Assistance Policy - PNAS.